Improved Antioxidative, Anti-Inflammatory, and Antimelanogenic Effects of Fermented Hydroponic Ginseng with Bacillus Strains - Ji-Young Park; Myung Wook Song; Kee-Tae Kim; Hyun-Dong Paik (MDPI AG, 2022)
Compared with traditionally cultured ginseng, hydroponic ginseng (HG) contains more remarkable bioactive compounds, which are known to exert diverse functional effects. This study aimed to enhance the multifunctional effects, including the antioxidative, anti-inflammatory, and antimelanogenic effects, exhibited by fermented HG with Bacillus strains, such as Bacillus subtilis KU43, Bacillus subtilis KU201, Bacillus polyfermenticus SCD, and Bacillus polyfermenticus KU3, at 37 °C for 48 h. After fermentation by B. subtilis KU201, the antioxidant activity, determined using ABTS and FRAP assays, increased from 25.30% to 51.34% and from 132.10% to 236.27%, respectively, accompanied by the enhancement of the phenolic compounds and flavonoids. The inflammation induced in RAW 264.7 cells by lipopolysaccharide (LPS) was ameliorated with fermented HG, which regulated the nitric oxide (NO), prostaglandin E2 (PGE2), and proinflammatory markers (tumor necrosis factor (TNF)-α, and interleukin (IL)-1β and IL-6). The treatment with fermented HG inhibited the melanin accumulation in B16F10 cells induced by α-melanocyte-stimulating hormone (α-MSH) by controlling the concentrations of melanin synthesis and tyrosinase activity. These results indicate that the HG exhibited stronger antioxidative, anti-inflammatory, and antimelanogenic effects after fermentation. Consequently, HG fermented by Bacillus strains can potentially be used as an ingredient in cosmetological and pharmaceutical applications.